Influence of summer mungbean genotypes on grain yield and resource-use efficiency in Kandahar province of Afghanistan - Noorzai, Amin Ullah; Choudhary, Anil K. (Annals of Agricultural Research, 2017)
A field experiment was conducted at Experimental Farm of Afghanistan National AgriculturalSciences and Technology University (ANASTU), Kandahar, Afghanistan during April-June, 2015to work-out the grain yield and resource-use efficiency of mungbean varieties viz. Mai-2008, Mash-2008, NM-94, NM-98 and local cultivar 'Kunduzy' under semi-arid conditions of Kandahar. Theresults indicated that Mash-2008 exhibited significantly highest grain yield while Kunduzy exhibitedminimum seed yield. The Mash-2008 yielded 5.0, 34.9, 34.5 and 48% more yield as compared toMai-2008, NM-98, NM-94 and 'Kunduzy', respectively. The mungbean genotypes showed significantdifferences for total water-use efficiency (TWUE), irrigation water-use efficiency (IWUE) andeconomic water productivity (WPE). Mash-2008 exhibited highest TWUE (9.9 kg ha–1 mm–1), IWUE(10.6 kg ha–1 mm–1) and WPE (644 AFN ha–1 mm–1) while 'Kunduzy' recorded minimum TWUE (6.7kg ha–1 mm–1), IWUE (7.2 kg ha–1 mm–1) and WPE (434 AFN ha–1 mm–1). Overall, Mash-2008outperformed in terms of grain yield, production-efficiency, monetary-efficiency, total water-useefficiency (TWUE), irrigation water-use efficiency (IWUE) and economic water productivity (WPE)over other mungbean cultivars in semi-arid conditions of Afghanistan.